Molecular Mechanisms of Intercellular Dissemination of Bacterial Pathogens. Issue 2 (February 2021) - Dowd, Georgina C.; Mortuza, Roman; Ireton, Keith
Abstract : Several intracellular bacterial pathogens, including Listeria monocytogenes, Shigella flexerni, and Rickettsia spp. use an actin-based motility process to spread in mammalian cell monolayers. Cell-to-cell spread is mediated by protrusive structures that contain bacteria encased in the host cell plasma membrane. These protrusions, which form in infected host cells, are internalized by neighboring cells. In this review, we summarize key findings on cell-to-cell spread, focusing on recent work on mechanisms of protrusion formation and internalization. We also discuss the dynamic behavior of bacterial populations during spread, and highlight recent findings showing that intercellular spread by an extracellular bacterial pathogen. Highlights: Cell-to-cell spread of the intracellular bacterial pathogens Listeria, Shigella, and Rickettsia involves manipulation of cortical tension in mammalian cell monolayers. Listeria exploits the host process of polarized exocytosis to initiate and elongate protrusions that mediate cell-to-cell spread. Internalization of protrusions of Listeria or Shigella involves bacterial manipulation of host endocytic proteins that form caveolae or clathrin-coated pits. Intercellular spread of Listeria is accelerated by rare pioneer bacteria that rapidly translocate in host cell monolayers. The extracellular pathogen enterohemorraghic E. coli uses protrusive structures called 'pedestals' to promote cell-to-cell spread.